2019
DOI: 10.1590/s1984-29612019069
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Rickettsia genus in chigger mites (Trombidiformes: Trombiculidae) collected on small mammals in southeastern brazilian

Abstract: Chiggers are ectoparasites of vertebrates and may cause trombiculiasis or transmit pathogens to their hosts. Specimens collected from rodents and marsupials were morphologically identified as Herpetacarus hertigi, Eutrombicula tinami, Kymocta sp., Quadraseta brasiliensis, Quadraseta falconensis, Quadraseta flochi, Quadraseta mackenziei, Quadraseta pazca, Quadraseta trapezoides, Quadraseta sp., Serratacarus sp., and Trombewingia bakeri. These mites were submitted individually to molecular analyses for the detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
8
1
Order By: Relevance
“…In this study, we provide the first evidence of Rickettsia infection in chiggers collected from rodents within North America, a significant extension of recent work finding rickettsial DNA in trombiculid mites from South America and Asia [ 10 , 31 , 32 ]. Nucleotide sequence analyses of Rickettsia -specific 23S-5S IGS, 17 kDa, and gltA gene fragments indicated the amplicons from these chiggers were closely related to those in R. felis , R. conorii , R. typhi , and unidentified Rickettsia species.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In this study, we provide the first evidence of Rickettsia infection in chiggers collected from rodents within North America, a significant extension of recent work finding rickettsial DNA in trombiculid mites from South America and Asia [ 10 , 31 , 32 ]. Nucleotide sequence analyses of Rickettsia -specific 23S-5S IGS, 17 kDa, and gltA gene fragments indicated the amplicons from these chiggers were closely related to those in R. felis , R. conorii , R. typhi , and unidentified Rickettsia species.…”
Section: Discussionmentioning
confidence: 63%
“…The most frequently detected rickettsial species in our study, Rickettsia felis , is globally distributed and was found in fleas, mosquitoes, ticks, and chigger mites [ 31 ]. There is increasing evidence that chiggers could be vectors of transitional group rickettsiae, because of their discovery in a variety of field-collected chiggers [ 10 , 32 ]. Several other rickettsiae known to infect humans, namely R. japonica , R. akari , R. felis , R. conorii , R. typhi , and other Rickettsia spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larvae were collected from the colilargo Oligoryzomys sp. Bangs, 1900 (Mammalia: Rodentia) in Brazil [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Parasite carrying a novel bacterium Candidatus Rickettsia colombianensi. Larvae were collected from the South American water rat Nectomys squamipes (Brants, 1827) (Mammalia: Rodentia) in Brazil [ 76 ].…”
Section: Resultsmentioning
confidence: 99%